MAPPING THE LANDSCAPE OF PROPRIOCEPTION RESEARCH IN GYMNASTICS: A BIBLIOMETRIC ANALYSIS AND SYSTEMATIC REVIEW - Andrea Fallas-Campos; Jesús Muñoz-Jiménez; Daniel Rojas-Valverde; Rodrigo Yáñez-Sepúlveda; Kiko León-Guzmán (Science of Gymnastics Journal)
Proprioception is a fundamental aspect of human movement and body awareness. The body’s ability to perceive its position in space enables accurate limb movement and balance control. Purpose: This study aims to provide a comprehensive overview of the current state of knowledge and to analyze bibliometric data related to proprioception in gymnastics and acrobatics. The study consists of two phases: (1) a bibliometric review based on data from the Web of Science and (2) a systematic review using Web of Science, PubMed, and Scopus databases. The search terms "gymnast*" and "propriocep*" were used to identify relevant publications. Out of 164 studies, 29 were included for data extraction, comprising 1,379 participants of various ages, sports, physical activity levels, and physical conditions.